2,2′-Dimethyl-1,1′-[2,2-bis(bromomethyl)propane-1,3-diyl]dibenzimidazole hemihydrate - Yong-Sheng Yan; Ling Liu; Shen-Tang Wang; Xing Wang; Chun-Bo Liu (Acta Crystallographica Section E, 2012)
The title compound, C21H22Br2N4·0.5H2O, contains two benzimidazole groups which may provide two potential coordination nodes for the construction of metal–organic frameworks. The mean planes of the two imidazole groups are almost perpendicular, with a dihedral angle of 83.05 (2)°, and adjacent molecules are linked into a one-dimensional chain by π–π stacking interactions between imidazole groups of different molecules [centroid-to-centroid distances of 3.834 (2) and 3.522 (2) Å].